ENVIRONMENTAL VIRTUE ETHICS FOR THE ANTHROPOCENE IN BARBARA KINGSOLVER’S FLIGHT BEHAVIOR - Xu Lan; Zainor Izat Zainal (PEOPLE: International Journal of Social Sciences, 2026)
The Anthropocene prompts introspection of human roles, demanding a reawakening of environmental responsibility and humans’ internal motivation to influence the future of the earth. In environmental virtue ethics, human beings are regarded as the source of environmental crisis. Through textual analysis, this paper focuses on emotions and actions exhibited by Dellarobia Turnbow, the protagonist in Barbara Kingsolver’s Flight Behavior (2012). Being a Pulitzer Prize-winning author of 2023, Kingsolver expresses her ethical advocation through the portrayal of Dellarobia. To examine how Dellarobia becomes an environmentally virtuous person, this study employs Ronald Sandler’s (2007) responsive and productive virtue ethics, which are openness and courage. The study reveals that Dellarobia cultivates openness by positively responding to her emotions towards the environment and allowing emotions as a form of judgement of value. Moreover, she cultivates courage by confronting the uncertainty of the future and making efforts to take actions while knowing her limitations. Thus, this study underscores the significance of internalizing principles and cultivating virtues both for the environment and humans’ flourishing in the Anthropocene. As a tentative application of environmental virtue ethics for the Anthropocene, this study reveals Kingsolver’s endeavor of setting fictional characters as environmental virtue exemplars to inspire humans’ active and constant contribution to a promising future.